Trichostatin A Promotes the Conversion of Astrocytes to Oligodendrocyte Progenitors in a Defined Culture Medium - Zare, Leila (Iran J Pharm Res, 2019)
The generation of oligodendrocyte progenitor cells (OPCs) offers tremendous opportunities for cell replacement therapy in demyelinating diseases such as multiple sclerosis (MS) and spinal cord injury. Recently, the prospect of reprogramming terminally differentiated adult cells towards another mature somatic cell or progenitor cells without an intermediate pluripotent state has been of interest. Trichostatin A is a histone deacetylase inhibitor which opens the chromatin and facilitates the transcription of silence genes. In this study, we have treated human astrocytes line U87 and primary culture of mouse astrocytes with TSA for 12 h, prior their transfer to OPC induction medium. Then we evaluated the morphology and the fate of the treated astrocytes at post-treatment days. Both cell lines acquired OPC morphology and expressed OPC specific markers. Following transfer to differentiation medium, U87-derived iOPCs differentiated to oligodendrocyte like cells and expressed PLP as a mature oligodendrocyte marker. Our results introduced TSA as an inducer for production of OPCs from astrocytes and could be considered a potential way for the treatment of demyelinating diseases.